Brachyspira pilosicoli bloodstream infections: Case report and review of the literature - Brun-Buisson Christian; Legrand Patrick; Thille Arnaud; Bait-Merabet Lilia; Cattoir Vincent (BMC, 2008)
Abstract Brachyspira pilosicoli is the etiologic agent of human and animal intestinal spirochetosis and is rarely implicated as a cause of bacteremia. Here, we describe the case of a B. pilosicoli spirochetemia in a 53-year-old male patient suffering from cardiogenic shock. This fastidious bacterium was isolated from blood, likely after translocation from the intestinal tract. Blood cultures were positive after 5 days of incubation (one day after the patient's death), highlighting the problem of the recovery of such type of fastidious bacterium. Identification was achieved by molecular methods (16S rRNA sequencing). A review of the English literature found only 8 cases of bacteremia caused by B. pilosicoli, mostly in immunocompromised or critically ill patients. Finally, difficulties in rapid and accurate diagnosis of B. pilosicoli bloodstream infections, in vitro antimicrobial susceptibility of human clinical isolates, and therapeutic options are discussed.